Eutrophication influences diversity and community-level change points of mycoplankton in subtropical estuaries - Zhong, Jiehao; Chen, Qingxiang; Deng, Xiaojie; Guan, Yongpeng; He, Qing; Nethmini, Rajapakshalage Thashikala; Tang, Jing; Hou, Qinghua; Li, Xiaolei; Jiang, Gonglingxia; Huang, Laizhen; Dong, Ke; et al. (Frontiers in Microbiology, 2025)
Mycoplankton are essential for biogeochemical cycles in natural water bodies. However, the distribution of the mycoplanktonic community and its community-level change points in subtropical estuaries remain unclear. In this study, we employed 18S rRNA high-throughput sequencing to explore the mycoplanktonic community structure and environmental thresholds in the Dafengjiang River Estuary. Agaricostilbomycetes and Saccharomycetes are the dominant classes in the Dafengjiang River Estuary. The alpha and beta diversities of the mycoplanktonic communities showed significant differences (p < 0.05) across the seasons. Distance-based redundancy analysis (db-RDA) suggested that the main driver of the total community was eutrophication level, and the key factors for oligotrophication, medium eutrophication, and high eutrophication were dissolved inorganic phosphorus (DIP), ammonium (NH4+), and chlorophyll-a (Chl-a), respectively. Threshold Indicator Taxa Analysis (TITAN) exhibited the community-level change points of mycoplankton along the eutrophication gradients were DIP (6–15.5 μg/L), NH4+ (61.5–62.5 μg/L) and Chl-a (2.55–9.3 μg/L), respectively. Random forest analysis revealed that Rhizophydium, Aspergillus and Vanrija were sensitive to eutrophication status and could serve as bioindicator genera for environmental changes. Overall, our study enhances our understanding of the diversity and community-level change points of mycoplankton in subtropical estuaries and lays the theoretical foundation for the environmental monitoring of subtropical estuaries.